The evolutionary history of polycotylid plesiosaurians. Issue 3 (28th March 2018) - Fischer, V.; Benson, R. B. J.; Druckenmiller, P. S.; Ketchum, H. F.; Bardet, N.
Abstract : Polycotylidae is a clade of plesiosaurians that appeared during the Early Cretaceous and became speciose and abundant early in the Late Cretaceous. However, this radiation is poorly understood. Thililua longicollis from the Middle Turonian of Morocco is an enigmatic taxon possessing an atypically long neck and, as originally reported, a series of unusual cranial features that cause unstable phylogenetic relationships for polycotylids. We reinterpret the holotype specimen of Thililua longicollis and clarify its cranial anatomy. Thililua longicollis possesses an extensive, foramina-bearing jugal, a premaxilla–parietal contact and carinated teeth. Phylogenetic analyses of a new cladistic dataset based on first-hand observation of most polycotylids recover Thililua and Mauriciosaurus as successive lineages at the base of the earliest Late Cretaceous polycotyline radiation. A new dataset summarizing the Bauplan of polycotylids reveals that their radiation produced an early burst of disparity during the Cenomanian–Turonian interval, with marked plasticity in relative neck length, but this did not arise as an ecological release following the extinction of ichthyosaurs and pliosaurids. This disparity vanished during and after the Turonian, which is consistent with a model of 'early experimentation/late constraint'. Two polycotylid clades, Occultonectia clade nov. and Polycotylinae, survived up to the Maastrichtian, but with low diversity.